2017
DOI: 10.1177/0146167216688213
|View full text |Cite
|
Sign up to set email alerts
|

Sage on the Stage

Abstract: Who presents at conferences matters. Presenting research benefits speakers, and presenters shape the conclusions audiences draw about who can succeed in a field. This is particularly important for members of historically underrepresented or disadvantaged groups, such as women. We investigated gender representation over a 13-year period among speakers at the largest social and personality psychology conference. On average, women were underrepresented as speakers, though this effect diminished over time. Chairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 51 publications
6
20
1
Order By: Relevance
“…Gender balance in oral presentations at SMBE conferences has gradually improved since 2001, in agreement with what has been observed for other conferences ( Schroeder et al. 2013 ; Casadevall and Handelsman 2014 ; Arnold 2015 ; Johnson et al. 2017 ; Débarre et al, forthcoming).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Gender balance in oral presentations at SMBE conferences has gradually improved since 2001, in agreement with what has been observed for other conferences ( Schroeder et al. 2013 ; Casadevall and Handelsman 2014 ; Arnold 2015 ; Johnson et al. 2017 ; Débarre et al, forthcoming).…”
Section: Discussionsupporting
confidence: 84%
“…Previous work on scientific conferences has shown that women were underrepresented among the speakers ( Schroeder et al. 2013 ; Casadevall and Handelsman 2014 ; Johnson et al. 2017 ; Débarre et al, forthcoming).…”
Section: Introductionmentioning
confidence: 97%
“…One analysis found that across six disciplines (including psychology), men were 1.2 times more likely to be invited as colloquium speakers at the top 50 universities in the United States ( Nittrouer et al, 2018 ); these effects could not be explained by the more senior status of men, by women placing less value on colloquium invitations, or by women being more likely than men to decline such invitations. Relative to the base rates of women members in the Society for Personality and Social Psychology, women were underrepresented as speakers in accepted symposia across 13 years of the organization’s annual meeting ( Johnson, Smith, & Wang, 2017 ). Note, however, that women’s representation in accepted compared with rejected symposia was similar for the 2 years of data available.…”
Section: Gender Gaps In Psychological Sciencementioning
confidence: 99%
“…Childcare issues also impact women's decisions to accept a speaking invitation (Schroeder et al, 2013). Alongside these personal barriers, professional obstacles to travel include insufficient institutional resources as well as being less likely than their male peers to be invited speakers at conferences, to be asked to chair conference sessions, to have a paper accepted at a conference, or to be asked to speak at departmental colloquia (Johnson, Smith, and Wang, 2017;Kalejta and Palmenberg, 2017;Nittrouer et al, 2017;Schroeder, et al, 2013).…”
Section: Organizational Intersections Of Gender Race and National Originmentioning
confidence: 99%